2001
DOI: 10.1080/003655901750170362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thromboxane and Nitric Oxide Blockade on Renal Blood Flow Increase during Volume Expansion in Hydronephrotic Rats

Abstract: It is concluded that a thromboxane- and/or nitric oxide-dependent RBF redistribution takes place in hydronephrotic kidneys during volume expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In our previous studies, we demonstrated that hydronephrosis, induced by partial unilateral obstruction, leads to the development of hypertension in both rats and mice [ 9 , 10 ]. Underlying pathological mechanisms in this model include altered prostaglandin and thromboxane signaling [ 35 , 36 ] in the diseased kidney together with oxidative stress and reduced NO bioavailability [ 12 15 ]. To the best of our knowledge, the above-mentioned pathological mechanisms have never been investigated in patients with hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we demonstrated that hydronephrosis, induced by partial unilateral obstruction, leads to the development of hypertension in both rats and mice [ 9 , 10 ]. Underlying pathological mechanisms in this model include altered prostaglandin and thromboxane signaling [ 35 , 36 ] in the diseased kidney together with oxidative stress and reduced NO bioavailability [ 12 15 ]. To the best of our knowledge, the above-mentioned pathological mechanisms have never been investigated in patients with hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The current retrospective study does not provide evidence regarding the mechanism, but in several previous experimental studies we have investigated underlying mechanisms contributing to hydronephrosis-induced hypertension. These include increased adenosine receptor-mediated contraction in the kidney, activation of renin-angiotensin-aldosterone system, enhanced renal sympathetic nerve activity (8,11,13), together with altered prostaglandin and thromboxane signaling (26,27), oxidative stress, and impaired nitric oxide signaling in the affected kidney (10–13). In support of these findings, our recent clinical study also demonstrated that children with hydronephrosis have abnormal prostaglandin and thromboxane signaling, oxidative stress, nitric oxide homeostasis (18), and increased plasmin levels in the urine (28).…”
Section: Discussionmentioning
confidence: 99%